National Resilience and State Defense Regarding Papuan Separatism - Aprillian, Bintang; Prilly, Kenysha Amanda; Yuliana, Nurul Siska; Nurhasanah, Nurhasanah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
The question of separatism in Papua has long been a critical issue affecting Indonesia's national security. This research aims to analyze the dynamics of separatism in Papua as well as the state defense strategy implemented by the Indonesian government in an effort to strengthen national resilience. This research uses qualitative methods with a literature study and documentation approach related to government policies, existing conflicts, and community responses. Research findings show that factors such as socioeconomic marginalization, ethnic identity, and colonial history contribute significantly to separatist aspirations in Papua. In addition, excessive security approaches often worsen rather than improve the security situation. In this context, the concept of national defense is not only understood as a military defense effort, but also as an inclusive strategy that promotes just social, economic and political development. This research recommends that an effective state defense strategy must involve constructive dialogue between the government and the Papuan people, recognition of the rights of indigenous peoples, and greater investment in human and infrastructure development. It is hoped that implementing this approach can reduce tensions and support stronger social integration between Papua and Indonesia as a whole.